Quality of life and its relationship with malnutrition in the elderly adult of the province of Ica - Rodríguez-Chacaltana, Francisco Willmer (2018)
Objetive: To determine the relationship between the quality of life and malnutrition of the elderly in the province of Ica in the year 2015. Methods: An observational, descriptive and prospective study was conducted in a population of 29 937 senior citizens of the province of Ica. The sample consisted of 138 older adults (60 to more years of age) who agreed to participate in the study by consent informed or informed consent of the relative. They were used; the WHOQOL-OLD survey and the Mini Nutritional Assessment to assess quality of life and nutritional status, respectively. Results: The unweighted total score obtained through the WHOQOL-OLD instrument was 87.0 or less in 50% of older adults. When older adults presented malnutrition, the score was 68.63 ± 3.40, when there was a risk of malnutrition it was 82.15 ± 1.34 and 90.08 ± 1.32 in the presence of satisfactory nutrition (p = 0.000). Conclusion: The quality of life of the elderly is related to the nutritional status. In the presence of malnutrition there is a lower overall quality of life and in its domains: functioning of the sensory, autonomy, past, present and future activities, social participation, privacy. DOI 10.25176/RFMH.v18.n4.1734